2012
DOI: 10.3109/02713683.2012.724512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glaucoma onChrna6Expression in the Retina

Abstract: Purpose Recent advances in technology now provide tools capable of tracking genome-wide expression changes occurring in progressive pathological processes. The present experiments were carried out to determine if acetylcholine receptor α 6 subunit (Chrna6) is a reliable retinal ganglion cell (RGC) marker in adult mouse eyes and if Chrna6 expression can be used to track progressive loss of RGCs, such as is observed in the DBA/2J glaucoma model. Methods Data sets derived from the BXD strains were used to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…2E,F). While Chrna6 has been previously demonstrated as an RGC subset marker 47 , we demonstrate here the presence of Anxa6 among a subset of these Pvalb + cells, where it has not been characterized before. We also investigated the expression of four genes which were correlated with Pvalb in one dataset, but not the other.…”
Section: Resultssupporting
confidence: 49%
“…2E,F). While Chrna6 has been previously demonstrated as an RGC subset marker 47 , we demonstrate here the presence of Anxa6 among a subset of these Pvalb + cells, where it has not been characterized before. We also investigated the expression of four genes which were correlated with Pvalb in one dataset, but not the other.…”
Section: Resultssupporting
confidence: 49%
“…For the in situ hybridization, we examined retinas 2 days after ONC (Figure 3B) and compared it to uninjured control retinas (Figure 3A). Using the Affymetrix 2-plex Quantigene View RNA ISH Tissue Assay kit, we labeled cells expressing the RGC marker Chrna6 blue and Sox11 red (Figure 3) (Munguba et al, 2013). In the control retina, many of the cells in the ganglion cell layer were heavily labeled for Chrna6 , and a few of the cells expressed marginal levels of Sox11 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we demonstrate that Sox11 is upregulated following retinal injury. For RGCs, there are many known markers, such as: Chrna6, Pou4f1, Tubb3, Thy1 , or Sncg (Barnstable and Drager, 1984; Gan et al, 1996; Mu et al, 2004; Surgucheva et al, 2008; Prasov and Glaser, 2012; Jiang et al, 2013; Munguba et al, 2013). Using these marker genes, we performed a meta-analysis of their expression in injured and uninjured retinas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous ONC studies have observed changes in gene expression within the retina [ 22 , 46 , 90 - 93 ] and glial based responses within the ON [ 29 ]. Analyzing the retina and ON simultaneously allowed the identification of individual clusters related to neuronal loss and regenerative failure within each tissue separately as well as allowed us to observe the temporal response of gene expression occurring in both the ON and retina with progressive injury to these two tissues.…”
Section: Discussionmentioning
confidence: 99%